Virulence of Escherichia coli in relation to host factors in women with symptomatic urinary tract infection. - Sandberg, T (1988)
The relationship between bacterial characteristics and the severity of urinary tract infection in adults has not been clarified. In this study, Escherichia coli strains (n = 178) were prospectively collected from women with community-acquired urinary tract infection. The isolates were identified by O:K:H serotype and characterized for adherence, hemolysin production, and serum bactericidal resistance. The patients had acute pyelonephritis with or without complicating factors and acute cystitis. Nine serotypes (O1:K1:H7, O1:K1:H-, O2:K1:H-, O4:K12:H1, O7:K1:H-, O9:K34:H-, O16:K1:H6, O16:K1:H-, and O75:K5:H-) comprised 65% of the strains in uncomplicated pyelonephritis, but were significantly less often encountered in complicated pyelonephritis or cystitis. Adherence was the single property most characteristic of the pyelonephritogenic clones. Adhesins specifically recognizing Gal alpha 1----4Gal beta-containing receptors occurred in 80% of strains in uncomplicated pyelonephritis, in 50% of strains in complicated infections, and in 37% of cystitis strains. Hemolysin production and serum resistance did not correlate with any disease pattern. Advanced age did not seem to reduce the selection of virulent E. coli to cause pyelonephritis. These results demonstrate in women a relationship between E. coli virulence and the severity of urinary tract infection analogous to that previously observed in pediatric populations and also illustrate the balance between host resistance and bacterial virulence in the urinary tract.